New detailed holocene paleomagnetic records with anomalous geomagnetic field behavior in Argentina - Nami, Hugo G. (2012)
Detailed palaeomagnetic studies were performed in several archaeological and geological sections dated with diverse relative and absolute methods. Data from 360 cores obtained in eight sites across eastern Argentina are reported. Characteristic remanence magnetization directions were determined by progressive alternating field demagnetization. Remanence directions showed anomalous geomagnetic field behavior far from the present magnetic field bearing oblique normal, oblique reverse and reverse polarities for the latest Pleistocene and Holocene, as well as evidence of possible field excursions recorded in several stratigraphic sections spanning ~11-0.5 kya. Computed virtual geomagnetic poles from those directions tend to be concentrated over North America, Europe, Eastern Asia, Africa and Australia. The hypothesis of the anomalous geomagnetic field directions is probably related with 14C fluctuations and solar activity.